Z‐scheme SnS2/CsPbBr3 Heterojunctions for Photoreduction CO2 Reaction and Related Photoinduced Carrier Behaviors. Issue 10 (27th July 2022) - Zhang, Rui; Li, Linjia; Li, YinYin; Wang, Dejun; Lin, Yanhong; Xie, Tengfeng
Abstract : CsPbBr3 perovskite exhibits potential application in photocatalytic CO2 reduction into valuable chemical fuels; however, enhancing carrier separation capability of the CsPbBr3 and fully understanding the CO2 reduction reaction process are still imperative. Herein, a new series of x SnS2 /CsPbBr3 nanocrystals (NCs)‐ y heterostructures are developed, which exhibit better catalytic activity in comparison with pure CsPbBr3 NCs. Interface and surface carrier dynamic investigation reveals that this heterojunction structure can effectively improve carrier separation efficiency. Based on the interfacial electric field direction of CsPbBr3 to SnS2, it is suggested that SnS2 /CsPbBr3 NC heterostructure satisfies Z‐scheme transfer dynamics. Meanwhile, by the aid of in situ surface photovoltage, it is experimentally confirmed there is dynamic carrier interaction between CO2 molecules and the SnS2 /CsPbBr3 NCs photocatalyst under irradiation, and a photocatalytic CO2 reduction mechanism is thus proposed. This work expands the awareness of the interaction between CO2 and the photocatalyst, which can be strongly influenced by carrier separation efficiency at the photocatalyst heterojunction. Abstract : SnS2 /CsPbBr3 heterojunction for photoreduction of CO2 is successfully constructed. According to the detection of the photogenerated carrier transfer behavior, photocarriers' transfer mechanism between SnS2 and CsPbBr3 meets the Z‐scheme mechanism. By the aid of in situ photovoltage, dynamic carrier interaction of CO2 adsorbed on the photocatalyst is suggested and understood.